Abundant exact solutions to the strain wave equation in micro-structured solids - Ali, Karmina K.; Yilmazer, R.; Bulut, H.; Akturk, Tolga; Osman, M. S. (World Scientific Publ Co Pte Ltd, 2021)
In this study, the strain wave equation in micro-structured solids which take an important place in solid physics is presented for consideration. The generalized exponential rational function method is used for this purpose which is one of the most powerful methods of constructing abundantly distinct, exact solutions of nonlinear partial differential equations. In micro-structured solids, wave propagation is based on the structure of the strain wave equation. As a consequence, we successfully received many different exact solutions, including non-topological solutions, periodic singular solutions, topological solutions, singular solutions, like periodic lump solutions. Furthermore, in order to better understand their physical interpretation, 2D, 3D, and counter plots are graphed for each of the solutions acquired.
Keywords: The strain wave equation; micro-structured solids; exact solutions; the generalized exponential rational function method